2009
DOI: 10.1590/s1984-46702009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and volume of water on the growth and development of tadpoles of Pleurodema diplolister and Rhinella granulosa (Amphibia: Anura)

Abstract: The capacity of tadpoles to reduce their metamorphosis time and body size in response to fluctuations in environmental variables of temporary ponds has been recorded in field and laboratory studies. The main alterations in this habitat are related to the decrease of the water level and increase in temperature. However, few studies tried to dissociate the effect of these two variables. The aim of the present study was to analyze simultaneously the effects of water volume reduction and temperature on the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Tadpoles exposed to low volumes of water increased their tail length and tail muscle depth as well as their growth and development rates. Maciel & Junca () found that the interaction between both factors (temperature and volume of water) had no influence on the development of larvae of Pleurodema diplolister and Chaunus granulosa and that the temperature was responsible for a reduction of the time of development in larvae of both species.…”
Section: Discussionmentioning
confidence: 99%
“…Tadpoles exposed to low volumes of water increased their tail length and tail muscle depth as well as their growth and development rates. Maciel & Junca () found that the interaction between both factors (temperature and volume of water) had no influence on the development of larvae of Pleurodema diplolister and Chaunus granulosa and that the temperature was responsible for a reduction of the time of development in larvae of both species.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the CHD9-mediated osteogenesis can be linked to the protective function against heat stress. Since water temperature is known to affect the timing of metamorphosis (Maciel and Juncá, 2009;Goldstein et al, 2017), the upregulation of CHD9 possibly be related to the body plan change associated with accelerated metamorphosis.…”
Section: Transcriptional and Translational Regulation Mechanismsmentioning
confidence: 99%
“…For animal populations, extrinsic factors such as climatic conditions clearly influence this relationship (ÁLVAREZ and NICIEZA, 2002;MACIEL and JUNCÁ, 2009). In these cases, ecological models (GAMITO, 1998) are indicated since weight gain rigorously reflects growth and its relationship with other variables that replace the time variable, such as length, height and width, often rules out environmental variations (SANTOS et al, 2007;GOMIERO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%